1989
DOI: 10.1295/polymj.21.809
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Assignments of the Methine Carbons in Polypropylene Using Two-Dimensional 13C-13C INADEQUATE NMR Spectroscopy

Abstract: ABSTRACT:The methine carbon resonances for atactic polypropylene were assigned based on methyl carbon resonances by two-dimensional 13 C-13 C INADEQUATE NMR spectroscopy. In combination with the analysis of 1 H decoupled 13 C NMR spectra of isotactic, syndiotactic and atactic polypropylenes, nine peaks observed were assigned to three heptad resonances (mmmmmm, mmmmmr, and rmmmmr), and six pentad resonances (mmmr, rmmr, mmrr, rmrr, mmrm, and mrmr and rr). KEY WORDSPolypropylene / Tacticity / 13 C NMR / Two-Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…In substantial agreement with Miyatake's attributions, 7 from the latter figure one can immediately deduce the following sequence of methine peaks (from low to high field): mmmmmm, mmmmmr, rmmmmr, mmmr, mmrr. On the other hand, quite surprisingly, the main component of the rmmr pentad appears to be overlapped with the intense and broad multiplet which includes the remaining six mr-and rr-centered pentads.…”
Section: Methine Peak Assignmentsupporting
confidence: 87%
See 3 more Smart Citations
“…In substantial agreement with Miyatake's attributions, 7 from the latter figure one can immediately deduce the following sequence of methine peaks (from low to high field): mmmmmm, mmmmmr, rmmmmr, mmmr, mmrr. On the other hand, quite surprisingly, the main component of the rmmr pentad appears to be overlapped with the intense and broad multiplet which includes the remaining six mr-and rr-centered pentads.…”
Section: Methine Peak Assignmentsupporting
confidence: 87%
“…6 Schilling and Tonelli, in particular, extended to the methine carbon the semiempirical equations based on the γ-gauche effect already adopted successfully for the methyl and methylene carbons. More recently, however, Miyatake et al 7 showed that Schilling and Tonelli's calculations disagree with experimental data obtained at a higher field (125 MHz), and proposed a partly different attribution.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…6.7) enables direct observation of neighboring 13 C-13 C correlation and has been applied to poly( vinyl alcohol) [20] and polypropylene [22]. 6.7) enables direct observation of neighboring 13 C-13 C correlation and has been applied to poly( vinyl alcohol) [20] and polypropylene [22].…”
Section: Methods Of Stereochemical Peak Assignmentsmentioning
confidence: 99%